2022
DOI: 10.1039/d2ra04653a
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-derived porous carbon/Co particle-based composites for high-performance microwave absorption

Abstract: A simple method that combines liquid–liquid phase separation and high-temperature pyrolysis has been developed for the synthesis of polyimide-derived porous carbon/Co particle-based composite absorbers (PIC/Co-800 and PIC/Co-1000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The peaks at 1376 cm −1 and 725 cm −1 indicate C–N–C stretching vibration. 33 After carbonization at 1000 °C, all the absorption peaks of PI disappeared in the IR spectrum. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 1376 cm −1 and 725 cm −1 indicate C–N–C stretching vibration. 33 After carbonization at 1000 °C, all the absorption peaks of PI disappeared in the IR spectrum. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] In our previous work, we demonstrated that PI-derived porous carbon prepared via LLPS maintains its porous structure during pyrolysis and revealed that increasing carbonization temperature impacts EMW absorption performance. 32 Herein, to further explore the conformational relationship between the types, contents, and morphology of nanoparticles and their EMW absorption performance, we varied iron acetylacetonate and acetylacetone cobalt(III) as the magnetic nanoparticles source, incorporating it into a polyamic acid solution through rapid stirring to form the composite material precursor. Aer LLPS treatment and high-temperature pyrolysis, the porous carbon/Fe 3 C (PIC/Fe 3 C) and porous carbon/FeCo alloy (PIC/FeCo) composite absorbers were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] In our previous work, we demonstrate that the polyimide-derived porous carbon (PPC) prepared by LLPS maintain its porous structure during pyrolysis method. 34 Herein, to further explore the conformational relationship between the internal crystalline structure and EMW absorbing properties of the fabricated PPC/Co, we change cobalt(III) acetylacetonate as cobalt source; it was added into polyamicacid solution by high-speed stirring to form composite precursor. Aer LLPS treatment and high-temperature pyrolysis, the porous carbon/cobalt nanoparticle composite absorbers were prepared.…”
Section: Introductionmentioning
confidence: 99%